2012
DOI: 10.4161/cbt.22002
|View full text |Cite
|
Sign up to set email alerts
|

EGFR tyrosine kinase inhibition induces autophagy in cancer cells

Abstract: Abbreviations: EGFR, epidermal growth factor receptor; TKI, tyrosine kinase inhibitor; NSCLC, non-small cell lung cancer; mTOR, mammalian target of rapamycin; LC3, microtubule-associated proteins 1A/1B light chain 3A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 26 publications
(35 reference statements)
10
82
1
Order By: Relevance
“…[12][13][14] Levine's group further demonstrated that the mechanism behind this observation is due to the binding of EGFR with BECN1. 12 Our data showed that EGFR controls the level of autophagic flux in hypoxia; a low level of autophagic flux protects cells from death whereas a high level of autophagic flux promotes cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] Levine's group further demonstrated that the mechanism behind this observation is due to the binding of EGFR with BECN1. 12 Our data showed that EGFR controls the level of autophagic flux in hypoxia; a low level of autophagic flux protects cells from death whereas a high level of autophagic flux promotes cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of EGFR inhibited autophagy [12][13][14] by triggering the binding of EGFR to the autophagy protein BECN1. 12 We examined the interaction between EGFR and BECN1 by immunoprecipitation (IP) in U87 cells.…”
Section: Egfr Regulates Hypoxia-induced Autophagy and Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study shows that defective autophagy may be a mechanism to confer resistance to inhibition of EGFR tyrosine kinase by cancer drugs. The co-treatment of these cells with rapamycin, a known inducer of autophagy, can partially restore sensitivity to EGFR tyrosine kinase inhibition, which suggests that activation of autophagy may be a viable strategy to treat or co-treat these types of cancer (20). These experiments suggest that a high level of autophagy might result in cell death in some types of tumors.…”
mentioning
confidence: 81%
“…Autophagy is generally thought to prevent cancer initiation but is also positioned to promote cancer cell survival upon metabolic stress (Brech et al, 2009; White, 2012). Rapamycin, an autophagy inducer, exhibits cytotoxic effects in cancer cells treated with EGFR tyrosine kinase inhibitors (TKIs), erlotinib or gefitinib (Fung et al, 2012; Gorzalczany et al, 2011). However, autophagy induced by EGFR TKIs or neutralizing antibody shows cytoprotective roles (Choi et al, 2013; Dragowska et al, 2013; Eimer et al, 2011; Han et al, 2011; Li and Fan, 2010; Li et al, 2010b; Sobhakumari et al, 2013; Zou et al, 2013), suggesting that EGFR TKIs (or neutralizing antibody) may induce autophagy by a mechanism distinct from rapamycin.…”
Section: Introductionmentioning
confidence: 99%